Rare Earth Doped Lanthanum Calcium Borate Polycrystalline Red Phosphors - H. H. Xiong; C. Zhu; X. Zhao; Z. Q. Wang; H. Lin (Advances in Materials Science and Engineering)
Single-phased Sm3+ doped lanthanum calcium borate (SmxLa2−xCaB10O19, SLCB, x=0.06) polycrystalline red phosphor was prepared by solid-state reaction method. The phosphor has two main excitation peaks located at 398.5 nm and 469.0 nm, which are nicely in accordance with the emitting wavelengths of commercial near-UV and blue light emitting diode chips. Under the excitation of 398.0 nm, the dominant red emission of Sm3+ in SLCB phosphor is centered at 598.0 nm corresponding to the transition of 4G5/2 → 6H7/2. The Eu3+ fluorescence in the red spectral region is applied as a spectroscopic probe to reveal the local site symmetry in the host lattice and, hence, Judd-Ofelt parameters Ωt  (t=2, 4) of Eu3+ in the phosphor matrix are derived to be 3.62×10-20 and 1.97×10-20 cm2, indicating a high asymmetrical and strong covalent environment around rare earth luminescence centers. Herein, the red phosphors are promising good candidates employed in white light emitting diodes (LEDs) illumination.